(untitled) (Al-Qamar, 2021)
ThThe Quran and the Sunnah prescribe death punishment for various offences, such as qatl-e-‘amd, apostasy (including blasphemy by a Muslim), ḥirābah when it involves qatl and zina by a muhsan. Moreover, there are instances of death punishment under the doctrine of fasād fi ‘l-ard for habitual offenders or when the offence was committed in a brutal and shocking manner. Muslim jurists divide these various instances of death punishment into three categories on the basis of the applicable legal principles. They are: Qisās, hudud and ta‘zīr (also called siyāsah). Although qiṣāṣ and hudud have some differences in legal consequences, yet they also have a few common legal consequences, such as the strict standard of proof, the special relaxations given to the accused (and even to the convict) and the immutable nature of the punishment. As opposed to qiṣāṣ and hudud, the matters related to ta‘zīr (or siyāsah) punishment have been left to the Muslim ruler who can prescribe details keeping in view the objectives, and within the constraints of the general principles, of Islamic law. Among these various consequences, the present paper focuses on the mode of execution of death punishment only.